ANALISIS DOMAIN BAI, DSS, DAN MEA PADA PENGUKURAN KUALITAS LAYANAN E-GOVERNMENT KABUPATEN PAMEKASAN MENGGUNAKAN FRAMEWORK COBIT 5.0 - Aang Kisnu Darmawan; Arisandi Dwi Harto (Jurnal Buana Informatika, 2019)
Abstract. This study aims to audit and evaluate the Dispendukcapil e-Government services in Pamekasan Regency using COBIT 5 Framework. The audit was conducted at the Dispendukcapil Office of Pamekasan Regency. The samples are four Districts and twelve Sub-districts / Villages that were considered quite representative. .The results show that overall capability audit results of the level of ICT services in the Pamekasan District Dispendukcapil are at level 3 (Establish) meaning that the process of ICT services has been implemented according to the existing ICT service standards. The detailed index value of the capability level of each domain is the BAI 2.85 domain (Established), DSS 2.50 domain (Established) and MEA domain 2.83 (Established). Field findings show that business processes in ICT governance of e-government services at the sub-district, village and village levels are at an incomplete level, meaning there is virtually no ICT governance process at that level. The need of fuller more authority on governance is suggested and recommended to be done at the sub-district and village / kelurahan levels by adding competent human resources in the ICT field to provide better e-government services.Keywords:E-Government, Capability Level, COBIT 5.0Abstrak. Penelitian ini bertujuan untuk melakukan audit dan evaluasi terhadap layanan e-Government Dispendukcapil Kabupaten Pamekasan dengan metode Framework COBIT 5. Audit dilakukan di Kantor Dispendukcapil Kabupaten Pamekasan. Sampel Layanan e-Government ialah empat Kecamatan dan 12 Kelurahan/Desa yang dianggap cukup representatif. Hasil penelitian menunjukkan secara keseluruhan hasil audit capability level layanan TIK Dispendukcapil kabupaten Pamekasan berada pada level 3 (Establish) dimana proses layanan TIK sudah terimplementasi sesuai standard layanan TIK yang ada. Rincian nilai indeks capability level masing-masing domain adalah domain BAI 2,85 (Established), domain DSS 2,50 (Established) dan domain MEA 2,83 (Established). Temuan menunjukkan bahwa proses bisnis dalam tata kelola TIK layanan e-government di tingkat kecamatan, kelurahan dan desa berada pada level 0 (incomplete), berarti hampir tidak ada sama sekali proses tata kelola layanan TIK di tingkatan tersebut. Diperlukan kewenangan yang lebih banyak pada tatakelola di tingkat kecamatan, dan desa/kelurahan dengan menambahkan SDM yang kompeten dalam bidang TIK untuk memberikan layanan e-government yang lebih baik.Kata Kunci: E-Government, Capability Level, COBIT 5.0.